Skin Microbiome Dynamics and Strain-Level Dysbiosis in Acne Vulgaris: Evidence from Diverse Egyptian Populations - Abdelaal, Rana (AUC Knowledge Fountain, 2026)
Background: Acne vulgaris, a prevalent chronic inflammatory disease, is a multifactorial disease comprising microbiological, immunological, and environmental factors. Recent findings highlight the importance of the skin microbiome, in particular the diversity and strain variability of Cutibacterium acnes, in the pathogenesis of acne. The Middle East and North Africa exhibit unique genetic and environmental traits; however, there is an absence of data concerning acne-related skin microbiome signatures in this region. Objectives: We aimed to characterize the facial skin microbiome of Egyptian acne patients and healthy controls, identify microbial signatures associated with the severity of acne, and compare skin microbial composition between urban and rural living. Methods: Cheek skin swabs were obtained from 45 acne patients (both urban and rural) and 25 healthy controls. Using Illumina NovaSeq, the V3-V4 region of the 16S rRNA gene was sequenced after extracting DNA. QIIME2 was used for investigating the structure of microbial communities. This included alpha and beta diversity, differential abundance testing, and predictive functional profiling. Results: Cutibacterium (66.3%) and Staphylococcus (16.1%) made up most of the skin microbiome. The relative abundance of C. acnes was not significantly different in healthy controls compared to acne patients across severity groups. In contrast, moderate-to-severe acne was associated with significantly higher alpha diversity compared to controls and mild acne. Based on a differential abundance analysis, specific C. acnes phylotype IA1 amplicon sequence variants (ASVs) were depleted in patients with moderate-to-severe acne, and in individuals who lived in rural compared to urban environments. Patients with acne in rural areas had higher alpha diversity and a distinct community composition. This was shown by an increase in environmental taxa like Kocuria and Peptostreptococcaceae and a decrease in Ralstonia and other taxa. Functional predictions revealed that urban samples were enriched in amino acid pathways. In contrast, rural samples showed enrichment in both amino acid and lipid metabolism pathways but had reduced energy metabolism pathways. Conclusions: Alterations in skin microbial composition and a depletion of specific C. acnes IA1 strains in association with acne severity are observed in the Egyptian population, rather than a global increase in C. acnes abundance. Environmental drivers such as urbanization play a key role in modulating skin microbiome diversity and can even alter the taxonomic and functional profile of skin microbial communities. These findings support a model in which acne pathogenesis involves both the loss of beneficial commensal C. acnes strains and the emergence of pathogenic variants. Emerging therapies should aim to restore microbial diversity and specifically target pathogenic strains, rather than broadly reducing C. acnes populations. Rural data suggest environmental microbial exposure can reshape the adult skin microbiome, supporting topical supplementation to enhance skin health.